Electric Motor Control: Innovations in Brushless DC Motors for Electric Vehicles - Isaac John Ibanga; Philip Sunday; Asuquo Mfonobong Rivenus (The Indonesian Institute of Science and Technology Research, 2026)
This study, titled Electric Motor Control: Innovations in Brushless DC Motors for Electric Vehicles, investigates advanced control technologies that enhance the performance, energy efficiency, and reliability of Brushless DC (BLDC) motors in electric vehicle (EV) applications. Employing a mixed-methods approach, the research integrates theoretical analysis, computational modeling, experimental validation, and real-world case studies. A comprehensive literature review from IEEE Xplore, ScienceDirect, SAE International, and industry reports forms the foundation, focusing on BLDC motor topologies, control strategies such as Field-Oriented Control (FOC) and Direct Torque Control (DTC), sensorless techniques, and emerging power electronics technologies including silicon carbide (SiC) and gallium nitride (GaN) devices. MATLAB/Simulink simulations are used to develop and test control algorithms, while electromagnetic and thermal analyses are conducted using ANSYS Maxwell and FLUX. Prototype validation involves hardware testing of a 1–10 kW BLDC motor system equipped with a DSP/FPGA controller and a SiC-based inverter under variable loads applied by a dynamometer. Key performance parameters, including torque ripple, energy efficiency, and thermal dissipation, are experimentally measured and statistically analyzed. The study also evaluates commercial EV systems, such as Tesla’s permanent magnet synchronous motors and Nissan Leaf’s BLDC implementations, to draw practical insights. Findings highlight that integrating advanced control methods, sensorless strategies, and high-performance power electronics significantly improves EV driving range, smoothness, and system durability. The results provide actionable insights for optimizing BLDC motor designs, addressing critical challenges in EV development, and supporting future innovations in sustainable transportation.